Dissertation Research and Writing for Built Environment Students - Naoum, S. G., (Shamil G.), author (London ; New York : Routledge, Taylor & Francis Group, 2019)
Dissertation Research and Writing for Built Environment Students is a step-by-step guide to get students through their final year research project. Trusted and developed over three previous editions, the new fourth edition shows you how to select a dissertation topic, write a proposal, conduct a literature review, select the research approach, gather the data, analyse and present the information and ultimately produce a well-written dissertation. The book simplifies dissertation research and writing into a process involving a sequence of learnable activities and divides the process into three parts. Part One covers the necessary groundwork, including: identifying the problem, writing a proposal and reviewing the literature. Part Two covers the research design and includes: approaches and techniques for data collection and constructing and sampling a questionnaire. Part Three covers: measurement of data, analysis of data with SPSS, structuring and writing the whole dissertation, and supervision and assessment. This new edition is packed with updated examples and research samples, making this the ideal resource for students involved in research in built environment subjects such as construction management, construction project management, facilities management, real estate, building surveying, quantity surveying and civil engineering.